Hematological Canvas: Unveiling the Secrets of Peripheral Blood Smear - Bharatkumar Anjaria, Mihir (Journal of Neonatal Surgery, 2025)
The present study sheds light on the diagnostic relevance of differences in the morphology of thrombocytes (platelets), white blood cells (WBCs), and red blood cells (RBCs) as seen on peripheral blood smears. This study conducted an extensive secondary literature on hematological disorders, centring on the shape and size of red and white blood cells and platelets, utilizing databases like PubMed, Scopus, and Google Scholar. Screening and diagnostic methodologies included basic laboratory tests and detailed microscopic examinations of peripheral blood smears. Notably, the study establishes a robust correlation between altered RBC morphology and various forms of anemia, underscoring the utility of red cell indices in classifying anemia into hypochromic microcytic, normochromic normocytic, and macrocytic categories. Each category signifies unique underlying causes and mechanisms impacting red blood cell functionality and overall health. Further, the study delves into WBC differentiation, highlighting how deviations in leukocyte count and morphology can signal immune dysfunction or hematological malignancies such as leukemia and lymphoma. It addresses the quantitative and qualitative changes in leukocytes, contributing to a deeper understanding of leukocyte disorders and their implications for patient health. Moreover, the research emphasizes the critical role of thrombocytes in diagnosing bleeding and clotting disorders through the examination of platelet count and morphology. It sheds light on conditions associated with thrombocytopenia and the diagnostic value of observing platelet size variations, which can hint at a variety of health issues ranging from production anomalies to increased platelet turnover.